A neural mediator of human anxiety sensitivity. Issue 10 (6th July 2015) - Harrison, Ben J.; Fullana, Miquel A.; Soriano‐Mas, Carles; Via, Esther; Pujol, Jesus; Martínez‐Zalacaín, Ignacio; Tinoco‐Gonzalez, Daniella; Davey, Christopher G.; López‐Solà, Marina; Pérez Sola, Victor; Menchón, José M.; Cardoner, Narcís
Abstract: Advances in the neuroscientific understanding of bodily autonomic awareness, or interoception, have led to the hypothesis that human trait anxiety sensitivity (AS)—the fear of bodily autonomic arousal—is primarily mediated by the anterior insular cortex. Despite broad appeal, few experimental studies have comprehensively addressed this hypothesis. We recruited 55 individuals exhibiting a range of AS and assessed them with functional magnetic resonance imaging (fMRI) during aversive fear conditioning. For each participant, three primary measures of interest were derived: a trait Anxiety Sensitivity Index score; an in‐scanner rating of elevated bodily anxiety sensations during fear conditioning; and a corresponding estimate of whole‐brain functional activation to the conditioned versus nonconditioned stimuli. Using a voxel‐wise mediation analysis framework, we formally tested for 'neural mediators' of the predicted association between trait AS score and in‐scanner anxiety sensations during fear conditioning. Contrary to the anterior insular hypothesis, no evidence of significant mediation was observed for this brain region, which was instead linked to perceived anxiety sensations independently from AS. Evidence for significant mediation was obtained for the dorsal anterior cingulate cortex—a finding that we argue is more consistent with the hypothesized role of human cingulofrontal cortex in conscious threat appraisal processes, including threat‐overestimation. This study offers an important neurobiological validation of the AS construct and identifies a specific neural substrate that may underlie high AS clinical phenotypes, including but not limited to panic disorder. Hum Brain Mapp 36:3950–3958, 2015 . © 2015 Wiley Periodicals, Inc.